Penerapan Metode Terapi Bermain Melalui Permainan Balok untuk Meningkatkan Kemampuan Sosial Anak Tunagrahita Ringan Kelas I di SLB Kota Raja Kupang - Selan, Ot Bil Wilson; Wangge, Vinsensius; Tusalakh, Filips Robertson; Muna, Kristin Rambu Yaku; Maure, Nelci Rousineri Kartika; Ndosni, Flora Cherli; Bana, Marci Dorance (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research focuses on how to build the social skills of children with mild intellectual disabilities in building interaction with the surrounding environment, an important part of their cognitive and social development. In order for students to understand this concept better, they need effective and enjoyable learning. The purpose of this study is to improve the social skills of children with mild intellectual disabilities through the use of interesting and interactive building media (blocks). The method used is classroom action research (PTK), carried out in two cycles consisting of planning, action, observation and reflection. The subject of the study is first-grade students with mild disabilities at SLBN Kota Raja Kupang, and the focus is on improving their social skills with classmates. The results showed that the ability to socialize with friends and the environment improved significantly after using Terapin's Block Games. In each cycle, data is collected through initial and final tests, as well as observation of student learning activities. At the end of the second cycle, the average score of the students increased significantly, indicating the effectiveness of the use of block game media in learning. This study concludes that beam media can be an effective tool to improve the social abilities of shiva with mild intellectual disabilities